2021
DOI: 10.1097/iae.0000000000003238
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Association Between Choroidal Vessels and Choriocapillaris in Normal Eyes

Abstract: To determine the relationship between large-sized and medium-sized choroidal vessels and choriocapillaris using the three-dimensional choroidal vascularity index (3D CVI) and percentage of flow deficits (FD%).Methods: Prospective observational study. The main outcome measures included choroidal volume parameters (3D CVI, mean choroidal thickness, total choroidal volume, choroidal luminal volume, and choroidal stromal volume), choriocapillaris parameters (FD %, average area of FD, and FD count), and age and axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…However, in Cheong KX et al's study, which quanti ed the 3D-CVI of 50 subjects' fundus within a 30-degree range centered on the fovea, no correlation was found between 3D-CVI and age (P = 0.081) [12]. Similarly, Sun G et al's study quanti ed the 3D-CVI of 63 healthy subjects' choroids within a 3*3mm range centered on the fovea and found no correlation between 3D-CVI and age (r = 0.043, P = 0.741) [17]. Our study results differ from previous reports.…”
Section: Discussionmentioning
confidence: 92%
“…However, in Cheong KX et al's study, which quanti ed the 3D-CVI of 50 subjects' fundus within a 30-degree range centered on the fovea, no correlation was found between 3D-CVI and age (P = 0.081) [12]. Similarly, Sun G et al's study quanti ed the 3D-CVI of 63 healthy subjects' choroids within a 3*3mm range centered on the fovea and found no correlation between 3D-CVI and age (r = 0.043, P = 0.741) [17]. Our study results differ from previous reports.…”
Section: Discussionmentioning
confidence: 92%
“… 17 In healthy subjects, CT was also found to be significantly correlated with choriocapillaris parameters, including choriocapillaris flow deficit (CC FD) density ( r = 0.290, P = 0.021) and CC FD number ( r = -0.312, P = 0.013). 18 Using SS-OCT angiography, Zheng et al 19 reported that CT was stably correlated with choriocapillaris vessel density ( r = 0.70–0.77) in patients with AMD with or without reticular pseudodrusen. In healthy subjects and patients with glaucoma, other studies have found that CT was independently associated with ocular perfusion pressure after adjusting for refractory errors, suggesting that CT may indirectly reflect ocular perfusion status.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, choroidal thickness (ChT), CVV, and CVI for the entire 3D scanning areas were automatically quantified by a deep learning algorithm in the SS-OCTA device, same as in previous studies ( Figure 1 , Supplementary Figure S1 ) ( Yang et al, 2020 ; Sun et al, 2021 ). ChT was defined as the length between 10 μm above Bruch’s membrane and the choroid–sclera interface.…”
Section: Methodsmentioning
confidence: 99%
“…62, 8. doi:10. 1167/iovs.62.1.8 Xu, A., Sun, G., Duan, C., Chen, Z., andChen, C. (2021). Quantitative assessment of three-dimensional choroidal vascularity and choriocapillaris flow signal voids in myopic patients using SS-OCTA.…”
Section: Data Availability Statementmentioning
confidence: 99%